Specificity of the sialic acid-binding lectin from the snail Cepaea hortensis - Brossmer, Reinhard; Wagner, Manfred; Fischer, Edgar (The journal of biological chemistry, 1992)
The specificity of the sialic acid-binding lectin from the snail Cepaea hortensis, purified by affinity chromatography on fetuin-Sepharose, was studied by hemagglutination inhibition assay applying 32 sialic acid derivatives and 14 glycoproteins. 2-alpha-Methyl-9-O-acetyl-NeuAc was the most potent inhibitor, followed closely by 2-alpha-methyl-NeuAc and 2-alpha-benzyl-NeuAc. An axially orientated carboxyl group is a prerequisite for maximal lectin-sugar binding. Neither size nor polarity of the alpha-anomeric substituent significantly influenced inhibition potency. An intact sialic acid N-acetyl group is essential for optimal lectin-sugar interaction. The trihydroxypropyl side chain also is of great importance. However, a bulky hydrophobic substituent at the side chain like a 9-O-tosyl residue did not decrease binding to the lectin. The lectin did not distinguish between NeuAc alpha 2—-3Gal beta 1—-4Glc and NeuAc alpha 2—-6Gal beta 1—-4Glc. Among other sugars tested, only N-acetylglucosamine showed inhibition, although 50-fold less. The most potent glycoprotein inhibitors were those carrying O-chains only or preferentially, as ovine submaxillary mucin, bovine submaxillary mucin, and glycophorin A. Tamm-Horsfall protein was an exception being a strong inhibitor, although carrying only N-chains. Asialoglycoproteins were inactive. Glycoproteins containing the NeuAc alpha 2—-3Gal sequence inhibited the lectin as well as those with NeuAc alpha 2—-6GalNAc. From the results a model of the lectin's binding site for sialic acid is suggested.
Artikel-Version: 4. Januar 2021
Gesehen am 24.06.2024